ALLOMETRIC RELATIONSHIPS IN OLIVA OLIVA (LINNE) - kasinathan, K; Maruthamuthu, S; Tagore, J (Indian Journal of Fisheries, 2011)
AUometric relationships between shell height, shell width, aperture height, aperture width, total animal weight, wet flesh weight, dry flesh weight and shell weight in Oliva oliva were subjected to correlation coefficient analysis and results have been discussed. Analysis of covariance revealed significant difference between regression equations of males and females. There is significant difference in growth between the male and female of this species which was observed thrcSugh Mahalanobis’ D.2 test. When considered size-groupwise, the shell dimensions (shell height and width) of males and females grow isometrically up to 35.9 mm in size